Implementasi Terapi Bermain Brain Gym Untuk Meningkatkan MemoriJangka Pendek Pada Anak Usia Sekolah di Wilayah RT 007 / RW 07Kelurahan Tebet Barat - Dinda Amelia; Anggraeni, Fitri Anggraeni; Ambarwati, Dwi Ambarwati (The Health Researcher's Journal, 2024)
After a child acquires information, he needs planned and consistent stimulation such as brain gym therapy so that he can recall whathe knew before. This short-term memory is usually lost instantly. Short-term memory in children is very poor, especially in education.This short-term memory is very important for remembering. The purpose of this researcher is to analyze the differences before andafter the implementation of Brain Gym Play Therapy to improve short-term memory in school-age children in RT 007 / RW 07 TebetBarat Village. Method This research design and type of quantitative research. The population in this study amounted to 15 childrenand the sample in this study amounted to 4 respondents. The measuring instrument used in this study is the Wechsler IntelligienceScale for Childern-Fourth Edition (WSIC-IV) Observation Sheet which consists of forwad digits and backward digits.The results ofthis study increased short-term memory did not experience a significant increase when after the brain gym play therapy was performed.